Análise de correlação e concordância das estimativas de imunoglobulinas no colostro bovino obtidas por métodos indiretos - Ingryd Muniz de Oliveira (2023)
Immunoglobulins (Ig) are abundant proteins present in bovine colostrum, which play an essential role in the transfer of passive immunity to neonates, since the synepitheliochorial type of placenta in cattle prevents the passage of immunoglobulins in the prenatal phase. Thus, the administration of high immunological quality colostrum, that is, abundant in Ig, quickly and aseptically is essential for the good development of calves. Currently, there are some ways to analyze the immunological quality of colostrum, through laboratory tests (ELISA and RID) and indirect evaluation equipment, such as a colostrometer and digital and optical Brix refractometer, which, unlike previous methods, can be easily and quickly used in the routine of the farm itself. Due to the importance of evaluating the immunological quality of colostrum, as well as the need to evaluate the association and agreement between the indirect evaluation methods, the aim of this work was to compile information from the literature on the different methods of evaluating the immunological quality of bovine colostrum, including their advantages and disadvantages, identifying the association between the methods and the agreement between them. The results in the literature indicate that the indirect methods have a moderate to positive association with the direct ones and that there is still divergence in the literature regarding the intensity of the association between the indirect methods of evaluating the immunological quality of colostrum. Because the colostrometer is made of glass, it may represent an additional cost to producers, due to replacements. The Brix refractometer is a scientific device, used in laboratories and in industries, which offers highly accurate measurements. In order to evaluate the magnitude and direction of the association between the measurements obtained by the indirect evaluation equipment (colostrometer, digital and optical Brix refractometers), 224 colostrum samples collected from two farms (n1=31 and n2=193) were used. , the first consisting of females from the 2nd to 9th order of lactation, of which 15 were of the Holstein breed, 5 of the Jersey breed and 11 of the Holstein x Jersey cross (5 animals 15/16 Jersey and 6 animals 7/8 Jersey ), and the second farm, by Holstein heifers and cows, from the 1st to the 7th order of lactation. Statistical analyzes of Pearson's correlation and concordance between measurements obtained from the equipment were carried out in the R software (version 4.2.2) using the “cocor” and “psych” packages, with all analyzes conducted at a 5% significance level. The correlation between the equipment was positive, ranging from strong to very strong on farms 1 and 2, respectively: between digital and optical Brix refractometers (r2 = 0.984 and r2 = 0.967; p<0.05), between colostrometer and refractometer Digital Brix (r2 = 0.810 and r2 = 0.829; p<0.05) and between the colostrometer and optical Brix refractometer (r2 = 0.829 and r2 = 0.842; p<0.05). The results indicate that the readings between the indirect evaluation equipment are strongly and positively correlated, that is, higher reading values from one of the equipment are also expected from the others, as well as lower values obtained from one of the indirect evaluation equipment, as well. will occur in others. The magnitude of the association did not differ between farms, but differed between equipment, with a higher common correlation (r2 = 0.970; p<0.05) between digital and optical Brix refractometers and lower correlation values between these equipment and the colostrometer (r2 = 0.826 for digital Brix refractometer and colostrometer p < 0.05; r2 = 0.840; for optical Brix refractometer and colostrometer p < 0.05). These results can be justified by the greater variability in measurements obtained with the colostrometer (CV = 28.91% and CV = 23.22%, respectively on farms 1 and 2) in relation to digital Brix refractometers (CV = 15.80% on farm 1 and CV = 14.38% on farm 2) and optical (CV = 13.62% and CV = 12.12% on farms 1 and 2, respectively). Despite the strong correlation between the devices, the agreement between them was divergent. Most samples (greater than 95%) were classified as good quality colostrum, while 9.8 and 12% were classified as low quality by the optical and digital Brix refractometer, respectively, and 4% by the colostrometer. These results may indicate greater fragility in detecting values below 50 mg/ml in the colostrometer. Although none of the equipment evaluated is considered the gold standard, that is, it directly estimates the concentration of immunoglobulins, the greater variability observed for data obtained from the colostrometer, the fragility and difficulty of measuring the equipment, the need for optimal colostrum temperature to reading, it is suggested that the colostrometer readings are more conflicting, which could compromise an efficient colostrum production. In addition, the results obtained point to the relevance of using direct methods in order to verify the accuracy of indirect equipment.